2006
DOI: 10.1016/j.visres.2006.03.023
|View full text |Cite
|
Sign up to set email alerts
|

With a careful look: Still no low-level confound to face pop-out

Abstract: In this issue of Vision Research, VanRullen, R. (2006). On second glance: Still no high-level pop-out effect for faces. Vision Research, in press. challenges our earlier Vision Research paper, "At first sight: A high-level pop-out effect for faces" (Hershler, O., & Hochstein, S. (2005). At first sight: A high-level pop-out effect for faces. Vision Research, 45, 1707-1724). In that paper, we showed that faces pop-out from a great variety of heterogeneous distractors. This search must have been based on a holist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…Again, this idea does converge with work investigating higher-order pop out effects in visual search, such as has been found with affective distinctiveness. For example, Hansen and Hansen (1988) reported that angry faces popped out from a crowd, although the veracity of this effect is a matter of controversy (Hampton et al, 1989; Purcell et al, 1996; Fox et al, 2000; Hershler and Hochstein, 2005, 2006; VanRullen, 2006). In the auditory domain, very little is known about attentional pop out effects.…”
Section: Introductionmentioning
confidence: 99%
“…Again, this idea does converge with work investigating higher-order pop out effects in visual search, such as has been found with affective distinctiveness. For example, Hansen and Hansen (1988) reported that angry faces popped out from a crowd, although the veracity of this effect is a matter of controversy (Hampton et al, 1989; Purcell et al, 1996; Fox et al, 2000; Hershler and Hochstein, 2005, 2006; VanRullen, 2006). In the auditory domain, very little is known about attentional pop out effects.…”
Section: Introductionmentioning
confidence: 99%
“…When researchers have used other objects as distracters as opposed to inverted faces, the results are more promising (Hershler & Hochstein, 2005;Kuehn & Jolicoeur, 1994, Experiment 3) though controversial (see the exchange between VanRullen, 2006 andHochstein, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…If so, then human faces may be located more efficiently than faces of other species. Previous studies suggest a human face detection advantage (e.g., Hershler, Golan, Bentin, & Hochstein, 2010; Hershler & Hochstein, 2005, 2006; Rousselet, MacĂ©, & Fabre-Thorpe, 2003; Stein, Sterzer, & Peelen, 2012). Although it may be commonly accepted that human faces should be detected more efficiently than faces of other species, this has not been empirically tested in a context in which faces of different species are competing for attention.…”
mentioning
confidence: 96%